Powder metallurgy material and preparation method thereof
By adding pore-forming additives and specific sintering processes to iron-based powder metallurgical materials, the problem of lowering hardness when increasing porosity is solved, and the double improvement of hardness and porosity is achieved.
Patent Information
- Application Number
- CN202411866947.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-18
AI Technical Summary
While the existing powder metallurgical materials increase porosity, their hardness is reduced, making it difficult to meet the dual requirements of hardness requirements and porosity improvement.
Pore-forming additives are added to iron-based powder metallurgical materials, and the reaction of copper sulfate, titanium dioxide and silicon nitride in the reducing agent state is generated to generate porous materials, and combined with a specific sintering process, the porosity and hardness of the materials are improved.
While ensuring hardness requirements, it significantly improves the porosity of powder metallurgical materials, achieving better technical results.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of powder metallurgy, and in particular to a powder metallurgy material and a preparation method thereof. Background Art
[0002] Powder metallurgy mainly refers to porous, semi-dense or fully dense materials made by powder metallurgy process. Powder metallurgy materials have unique chemical composition and physical and mechanical properties that cannot be obtained by traditional melting and casting processes, such as controllable porosity, uniform material structure, no macro segregation, and one-time molding.
[0003] In the prior art, the hardness of powder metallurgy materials is directly related to their porosity. The surface macroscopic hardness of powder metallurgy products decreases with the increase of porosity. This is because the matrix material is weakened by the pores. When measuring the hardness, the indenter presses on the metal matrix and the pores at the same time, resulting in a significant reduction in the volume resisting the indenter, thereby reducing the ability of the material surface to resist plastic deformation, and the measured hardness value is low. In general, as the porosity increases, the corresponding hardness of powder metallurgy materials will also decrease.
[0004] Therefore, how to provide a powder metallurgy material and a preparation method thereof to improve the porosity of the metal metallurgical material while ensuring the hardness requirement is a technical problem that needs to be solved urgently by those skilled in the art. Summary of the invention
[0005] To this end, the present invention provides a powder metallurgy material and a preparation method thereof to solve the related technical problems existing in the prior art.
[0006] In order to achieve the above object, the present invention provides the following technical solutions: According to a first aspect of the present invention, a powder metallurgy material is provided, comprising the following raw materials in parts by weight: 0.5-1.1 parts of carbon nanotubes, 1.5-2.5 parts of copper, 1.8-3.2 parts of aluminum, 2.0-3.5 parts of nickel, 0.5-0.8 parts of titanium, 0.1-0.4 parts of pore-forming additives, based on 100 parts, the balance is iron.
[0007] Further, the following raw materials are included in parts by weight: 0.8-1.0 parts of carbon nanotubes, 1.7-2.1 parts of copper, 2.2-3.1 parts of aluminum, 2.4-3.3 parts of nickel, 0.6-0.8 parts of titanium, 0.2-0.4 parts of pore-forming additives, based on 100 parts, the balance is iron.
[0008] Furthermore, the pore-forming additive comprises the following processing steps: The raw materials include the following parts by weight: 30-50 parts of copper sulfate, 20-30 parts of titanium dioxide, 10-25 parts of silicon nitride and 3-5 parts of potassium borohydride; The processing steps include: First, weigh corresponding amounts of copper sulfate, titanium dioxide, silicon nitride and potassium borohydride; Secondly, copper sulfate, titanium dioxide and silicon nitride are placed in deionized water, the pH is adjusted to 7-8 with sodium hydroxide, potassium borohydride is added while stirring, and the temperature is controlled at 65-80°C after the addition is completed, stirring is continued for 1.5-4.0 hours, and the precipitate is collected by centrifugation and rinsed multiple times; Again, the above precipitate is transferred to a tube furnace, set the temperature to 130-160°C and dried for 3-5 hours, then gradually heated to 1100-1300°C and heated under argon protection for 3-12 hours; Finally, after cooling, the pore-forming additive is crushed and ground into powder and sieved through a 300-mesh screen.
[0009] Furthermore, the carbon nanotubes, copper, aluminum, nickel, titanium and iron are all sieved through 300 meshes.
[0010] According to a second aspect of the present invention, there is provided a method for preparing a powder metallurgy material, which is used to produce the powder metallurgy material as described above, comprising the following steps: (1) Mixing: Put the raw material components of powder metallurgy materials into a mixer to mix the raw materials evenly; (2) Cold pressing: adding the raw materials mixed in step (1) into the mold cavity, pressing and molding, and then demolding; (3) Sintering: The blank obtained by demolding in step (2) is sintered in a sintering furnace under nitrogen protection.
[0011] Furthermore, in step 1), the mixing speed is 130-150 rpm, and the mixing time is 1-2 h.
[0012] Furthermore, in step 2), the cold pressing pressure is 750-850 MPa, and the cold pressing holding time is 20-40 min.
[0013] Further, step 3) includes: Preheating stage: preheat the cold-pressed blank at a temperature of 110-130°C for 20 minutes; Heating stage: Heating rate is 35-50℃ / min, heating to 850℃ and then keeping warm for 45min; Sintering stage: heating rate 100℃ / min, heating to 1250-1320℃ and keeping warm for 2-3h.
[0014] Furthermore, in step 3), the nitrogen pressure is 0.3-0.5Mpa.
[0015] According to a third aspect of the present invention, there is provided a bearing, which is manufactured using the above method for preparing a powder metallurgy material.
[0016] The present invention has the following advantages: In the technical solution of the present application, a pore-forming additive is creatively added to the iron-based powder metallurgy material. The porous material is generated by reacting copper sulfate, titanium dioxide and silicon nitride in the state of a reducing agent. The porosity of the finished product can be increased during the processing of the powder metallurgy material. At the same time, in combination with the billet sintering method of the present application, its hardness can also meet the ideal requirements. DETAILED DESCRIPTION
[0017] The following is a description of the implementation of the present invention by specific embodiments. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] In order to solve the problem of mutual influence between porosity and hardness existing in the prior art, the present application creatively adds pore-forming additives separately, so that while ensuring that the raw material components are processed to meet the hardness requirements, the added pore-forming additives are used to increase the porosity, and the finished product achieves a better technical effect.
[0019] According to a first aspect of the present invention, a powder metallurgy material is provided, comprising the following raw materials in parts by weight: 0.5-1.1 parts of carbon nanotubes, 1.5-2.5 parts of copper, 1.8-3.2 parts of aluminum, 2.0-3.5 parts of nickel, 0.5-0.8 parts of titanium, 0.1-0.4 parts of pore-forming additives, based on 100 parts, the balance is iron.
[0020] Further, the following raw materials are included in parts by weight: 0.8-1.0 parts of carbon nanotubes, 1.7-2.1 parts of copper, 2.2-3.1 parts of aluminum, 2.4-3.3 parts of nickel, 0.6-0.8 parts of titanium, 0.2-0.4 parts of pore-forming additives, based on 100 parts, the balance is iron.
[0021] Further, the pore-forming additive comprises the following processing steps: The raw materials include the following parts by weight: 30-50 parts of copper sulfate, 20-30 parts of titanium dioxide, 10-25 parts of silicon nitride and 3-5 parts of potassium borohydride; The processing steps include: First, weigh corresponding amounts of copper sulfate, titanium dioxide, silicon nitride and potassium borohydride; Secondly, copper sulfate, titanium dioxide and silicon nitride are placed in deionized water, the pH is adjusted to 7-8 with sodium hydroxide, potassium borohydride is added while stirring, and the temperature is controlled at 65-80°C after the addition is completed, stirring is continued for 1.5-4.0 hours, and the precipitate is collected by centrifugation and rinsed multiple times; Again, the above precipitate is transferred to a tube furnace, set the temperature to 130-160°C and dried for 3-5 hours, then gradually heated to 1100-1300°C and heated under argon protection for 3-12 hours; Finally, after cooling, the pore-forming additive is crushed and ground into powder and sieved through a 300-mesh screen.
[0022] Furthermore, the carbon nanotubes, copper, aluminum, nickel, titanium and iron were all sieved through 300 mesh.
[0023] According to a second aspect of the present invention, there is provided a method for preparing a powder metallurgy material, which is used to produce the above powder metallurgy material, comprising the following steps: (1) Mixing: Put the raw material components of powder metallurgy materials into a mixer to mix the raw materials evenly; (2) Cold pressing: adding the raw materials mixed in step (1) into the mold cavity, pressing and molding, and then demolding; (3) Sintering: The blank obtained by demolding in step (2) is sintered in a sintering furnace under nitrogen protection.
[0024] Furthermore, in step 1), the mixing speed is 130-150 rpm, and the mixing time is 1-2 h.
[0025] Furthermore, in step 2), the cold pressing pressure is 750-850 MPa, and the cold pressing holding time is 20-40 min.
[0026] Further, step 3) includes: Preheating stage: preheat the cold-pressed blank at a temperature of 110-130°C for 20 minutes; Heating stage: Heating rate is 35-50℃ / min, heating to 850℃ and then keeping warm for 45min; Sintering stage: heating rate 100℃ / min, heating to 1250-1320℃ and keeping warm for 2-3h.
[0027] Furthermore, in step 3), the nitrogen pressure is 0.3-0.5Mpa.
[0028] According to a third aspect of the present invention, there is provided a bearing, which is manufactured using the above method for preparing a powder metallurgy material.
[0029] Based on the inventive ideas provided above, the present application provides the following embodiments to illustrate the technical effects of the present application.
[0030] Example 1 This embodiment provides a method for preparing a powder metallurgy material, which is used to produce a powder metallurgy material, comprising the following steps: Preparation of pore-forming additive: wherein the raw materials include the following parts by weight: 35 parts of copper sulfate, 23 parts of titanium dioxide, 18 parts of silicon nitride and 3 parts of potassium borohydride; The processing steps include: First, weigh corresponding amounts of copper sulfate, titanium dioxide, silicon nitride and potassium borohydride; Secondly, copper sulfate, titanium dioxide and silicon nitride are placed in deionized water, the pH is adjusted to 7-8 with sodium hydroxide, potassium borohydride is added while stirring, and the temperature is controlled at 65-80°C after the addition is completed, stirring is continued for 2 hours, and the precipitate is collected by centrifugation and rinsed multiple times; Again, the above precipitate was transferred to a tube furnace, set the temperature at 150°C for drying for 3 h, and then gradually heated to 1250°C for heating under argon protection for 6 h; Finally, after cooling, the pore-forming additive is crushed and ground into powder and sieved through a 300-mesh screen.
[0031] Preparation of other raw materials: including the following raw materials by weight: 0.8 parts of carbon nanotubes, 2.5 parts of copper, 1.8 parts of aluminum, 2.0 parts of nickel, and 0.8 parts of titanium are 100 parts, and the balance is iron. Each raw material component: carbon nanotubes, copper, aluminum, nickel, titanium, and iron are sieved through a 300-mesh sieve.
[0032] The specific processing steps of powder metallurgy materials are as follows: (1) Mixing: Put the raw material components of the powder metallurgy material into a mixer to mix the raw materials evenly; the mixing speed is 135 rpm and the mixing time is 1.5 h.
[0033] (2) Cold pressing: the raw materials mixed in step (1) are added into the mold cavity, pressed and then demolded; the cold pressing pressure is 795 MPa, and the cold pressing holding time is 30 min.
[0034] (3) Sintering: The blank obtained by demolding in step (2) is sintered in a sintering furnace under nitrogen protection and nitrogen atmosphere, and the nitrogen pressure is 0.3 MPa, including: Preheating stage: preheat the cold-pressed blank at a temperature of 115°C for 20 minutes; Heating stage: heating rate is 40℃ / min, heating to 850℃ and then keeping warm for 45min; Sintering stage: heating rate 100℃ / min, heating to 1263℃ and keeping warm for 3h.
[0035] The finished product was tested for hardness and density. Please see Table 1 for specific test results.
[0036] Example 2 This embodiment provides a method for preparing a powder metallurgy material, which is used to produce a powder metallurgy material, comprising the following steps: Preparation of pore-forming additive: wherein the raw materials include the following parts by weight: 40 parts of copper sulfate, 20 parts of titanium dioxide, 23 parts of silicon nitride and 4 parts of potassium borohydride; The processing steps include: First, weigh corresponding amounts of copper sulfate, titanium dioxide, silicon nitride and potassium borohydride; Secondly, copper sulfate, titanium dioxide and silicon nitride were placed in deionized water, the pH was adjusted to 7-8 with sodium hydroxide, potassium borohydride was added while stirring, and the temperature was controlled at 65-80°C after the addition was completed, stirring was continued for 2.5 hours, the precipitate was collected by centrifugation and rinsed several times; Again, the above precipitate was transferred to a tube furnace, set the temperature at 145°C for drying for 4 h, and then gradually heated to 1180°C for heating under argon protection for 10 h; Finally, after cooling, the pore-forming additive is crushed and ground into powder and sieved through a 300-mesh screen.
[0037] Preparation of other raw materials: including the following raw materials by weight: 1.0 part of carbon nanotubes, 2.1 parts of copper, 2.2 parts of aluminum, 3.3 parts of nickel, 0.6 parts of titanium, the balance being iron, are 100 parts. Each raw material component: carbon nanotubes, copper, aluminum, nickel, titanium and iron are sieved through a 300 mesh screen.
[0038] The specific processing steps of powder metallurgy materials are as follows: (1) Mixing: Put the raw material components of the powder metallurgy material into a mixer to mix the raw materials evenly; the mixing speed is 145 rpm and the mixing time is 1 h.
[0039] (2) Cold pressing: the raw materials mixed in step (1) are added into the mold cavity, pressed and then demolded; the cold pressing pressure is 832 MPa, and the cold pressing holding time is 25 min.
[0040] (3) Sintering: The blank obtained by demolding in step (2) is sintered in a sintering furnace under nitrogen protection and nitrogen atmosphere, and the nitrogen pressure is 0.4 MPa, including: Preheating stage: preheat the cold-pressed blank at 120°C for 20 minutes; Heating stage: heating rate is 45℃ / min, heating to 850℃ and then keeping warm for 45min; Sintering stage: heating rate 100℃ / min, heating to 1282℃ and keeping warm for 2.5h.
[0041] The finished product was tested for hardness and density. Please see Table 1 for specific test results.
[0042] Example 3 This embodiment provides a method for preparing a powder metallurgy material, which is used to produce a powder metallurgy material, comprising the following steps: Preparation of pore-forming additive: wherein the raw materials include the following parts by weight: 45 parts of copper sulfate, 25 parts of titanium dioxide, 21 parts of silicon nitride and 4.5 parts of potassium borohydride; The processing steps include: First, weigh corresponding amounts of copper sulfate, titanium dioxide, silicon nitride and potassium borohydride; Secondly, copper sulfate, titanium dioxide and silicon nitride were placed in deionized water, the pH was adjusted to 7-8 with sodium hydroxide, potassium borohydride was added while stirring, and the temperature was controlled at 65-80°C after the addition was completed, stirring was continued for 3.5 hours, the precipitate was collected by centrifugation and rinsed several times; Again, the above precipitate was transferred to a tube furnace, set at 135°C for drying for 4.8h, and then gradually heated to 1300°C for heating under argon protection for 5h; Finally, after cooling, the pore-forming additive is crushed and ground into powder and sieved through a 300-mesh screen.
[0043] Preparation of other raw materials: including the following raw materials by weight: 0.6 parts of carbon nanotubes, 1.7 parts of copper, 2.7 parts of aluminum, 3.0 parts of nickel, 0.5 parts of titanium, the balance being iron, are 100 parts. Each raw material component: carbon nanotubes, copper, aluminum, nickel, titanium and iron are sieved through a 300 mesh screen.
[0044] The specific processing steps of powder metallurgy materials are as follows: (1) Mixing: Put the raw material components of the powder metallurgy material into a mixer to mix the raw materials evenly; the mixing speed is 130 rpm and the mixing time is 2 h.
[0045] (2) Cold pressing: the raw materials mixed in step (1) are added into the mold cavity, pressed and then demolded; the cold pressing pressure is 846 MPa, and the cold pressing holding time is 22 min.
[0046] (3) Sintering: The blank obtained by demolding in step (2) is sintered in a sintering furnace under nitrogen protection and nitrogen atmosphere, and the nitrogen pressure is 0.4 MPa, including: Preheating stage: preheat the cold-pressed blank at a temperature of 125°C for 20 minutes; Heating stage: heating rate is 37℃ / min, heating to 850℃ and keeping temperature for 45min; Sintering stage: heating rate 100℃ / min, heating to 1295℃ and keeping warm for 2.3h.
[0047] The finished product was tested for hardness and density. Please see Table 1 for specific test results.
[0048] Example 4 This embodiment provides a method for preparing a powder metallurgy material, which is used to produce a powder metallurgy material, comprising the following steps: Preparation of pore-forming additive: wherein the raw materials include the following parts by weight: 50 parts of copper sulfate, 27 parts of titanium dioxide, 15 parts of silicon nitride and 5 parts of potassium borohydride; The processing steps include: First, weigh corresponding amounts of copper sulfate, titanium dioxide, silicon nitride and potassium borohydride; Secondly, copper sulfate, titanium dioxide and silicon nitride are placed in deionized water, the pH is adjusted to 7-8 with sodium hydroxide, potassium borohydride is added while stirring, and the temperature is controlled at 65-80°C after the addition is completed. Stirring is continued for 4 hours, and the precipitate is collected by centrifugation and rinsed multiple times; Again, the above precipitate was transferred to a tube furnace, set at 155°C for drying for 3.5 h, and then gradually heated to 1200°C for heating under argon protection for 8 h; Finally, after cooling, the pore-forming additive is crushed and ground into powder and sieved through a 300-mesh screen.
[0049] Preparation of other raw materials: including the following raw materials by weight: 1.1 parts of carbon nanotubes, 1.5 parts of copper, 3.1 parts of aluminum, 2.4 parts of nickel, 0.6 parts of titanium, 100 parts, the balance being iron. Each raw material component: carbon nanotubes, copper, aluminum, nickel, titanium and iron are sieved through a 300 mesh screen.
[0050] The specific processing steps of powder metallurgy materials are as follows: (1) Mixing: Put the raw material components of the powder metallurgy material into a mixer to mix the raw materials evenly; the mixing speed is 141 rpm and the mixing time is 1.3 h.
[0051] (2) Cold pressing: the raw materials mixed in step (1) are added into the mold cavity, pressed and then demolded; the cold pressing pressure is 790 MPa, and the cold pressing holding time is 36 min.
[0052] (3) Sintering: The blank obtained by demolding in step (2) is sintered in a sintering furnace under nitrogen protection and nitrogen atmosphere, and the nitrogen pressure is 0.5 MPa, including: Preheating stage: preheat the cold-pressed blank at a temperature of 126°C for 20 minutes; Heating stage: heating rate is 46℃ / min, heating to 850℃ and then keeping warm for 45min; Sintering stage: heating rate 100℃ / min, heating to 1313℃ and keeping warm for 2h.
[0053] The finished product was tested for hardness and density. Please see Table 1 for specific test results.
[0054] Comparative Example 1 This comparative example 1 follows the preparation method of Example 1, but does not add a pore-forming additive. The details are as follows: This comparative example provides a method for preparing a powder metallurgy material, which is used to produce a powder metallurgy material, comprising the following steps: Preparation of raw materials: including the following raw materials by weight: 0.8 parts of carbon nanotubes, 2.5 parts of copper, 1.8 parts of aluminum, 2.0 parts of nickel, and 0.8 parts of titanium are 100 parts, and the balance is iron. Each raw material component: carbon nanotubes, copper, aluminum, nickel, titanium, and iron are sieved through a 300-mesh sieve.
[0055] The specific processing steps of powder metallurgy materials are as follows: (1) Mixing: Put the raw material components of the powder metallurgy material into a mixer to mix the raw materials evenly; the mixing speed is 135 rpm and the mixing time is 1.5 h.
[0056] (2) Cold pressing: the raw materials mixed in step (1) are added into the mold cavity, pressed and then demolded; the cold pressing pressure is 795 MPa, and the cold pressing holding time is 30 min.
[0057] (3) Sintering: The blank obtained by demolding in step (2) is sintered in a sintering furnace under nitrogen protection and nitrogen atmosphere, and the nitrogen pressure is 0.3 MPa, including: Preheating stage: preheat the cold-pressed blank at a temperature of 115°C for 20 minutes; Heating stage: heating rate is 40℃ / min, heating to 850℃ and then keeping warm for 45min; Sintering stage: heating rate 100℃ / min, heating to 1263℃ and keeping warm for 3h.
[0058] The finished product was tested for hardness and density. Please see Table 1 for specific test results.
[0059] Table 1: Hardness and density test results of Examples 1-4 and Comparative Example 1
[0060] From Table 1, it can be seen that in Examples 1-4 where pore-forming additives are added, as the amount of addition increases, the density of the finished products is constantly decreasing, representing an increase in porosity, while in Comparative Example 1 where no pore-forming additives are added, the density is significantly higher than that of Examples 1-4. At the same time, when pore-forming additives are added, the hardness of Examples 1-4 is constantly decreasing, but from the overall decreasing trend, the decreasing range is not large. Of course, in Comparative Example 1 where no pore-forming additives are added, the hardness is the highest, but compared with Example 1 where pore-forming additives are added, under the same proportion, the hardness decreases less and the density decreases more, achieving the expected experimental effect.
[0061] In the technical solution of the present application, a pore-forming additive is creatively added to the iron-based powder metallurgy material. The porous material is generated by reacting copper sulfate, titanium dioxide and silicon nitride in the state of a reducing agent. The porosity of the finished product can be increased during the processing of the powder metallurgy material. At the same time, in combination with the billet sintering method of the present application, its hardness can also meet the ideal requirements.
[0062] Although the present invention has been described in detail above by general description and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.
Claims
1. A powder metallurgy material, characterized in that: The invention comprises the following raw materials in parts by weight: 0.5-1.1 parts of carbon nanotubes, 1.5-2.5 parts of copper, 1.8-3.2 parts of aluminum, 2.0-3.5 parts of nickel, 0.5-0.8 parts of titanium, 0.1-0.4 parts of pore-forming additives, based on 100 parts, the balance is iron.
2. The powder metallurgy material according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 0.8-1.0 parts of carbon nanotubes, 1.7-2.1 parts of copper, 2.2-3.1 parts of aluminum, 2.4-3.3 parts of nickel, 0.6-0.8 parts of titanium, 0.2-0.4 parts of pore-forming additives, based on 100 parts, the balance is iron.
3. The powder metallurgy material according to claim 2, characterized in that: The pore-forming additive comprises the following processing steps: The raw materials include the following parts by weight: 30-50 parts of copper sulfate, 20-30 parts of titanium dioxide, 10-25 parts of silicon nitride and 3-5 parts of potassium borohydride; The processing steps include: First, weigh corresponding amounts of copper sulfate, titanium dioxide, silicon nitride and potassium borohydride; Secondly, copper sulfate, titanium dioxide and silicon nitride are placed in deionized water, the pH is adjusted to 7-8 with sodium hydroxide, potassium borohydride is added while stirring, and the temperature is controlled at 65-80°C after the addition is completed, stirring is continued for 1.5-4.0 hours, and the precipitate is collected by centrifugation and rinsed multiple times; Again, the above precipitate is transferred to a tube furnace, set the temperature to 130-160°C and dried for 3-5 hours, then gradually heated to 1100-1300°C and heated under argon protection for 3-12 hours; Finally, after cooling, the pore-forming additive is crushed and ground into powder and sieved through a 300-mesh screen.
4. The powder metallurgy material according to claim 1, characterized in that: The carbon nanotubes, copper, aluminum, nickel, titanium and iron are all sieved through 300 meshes.
5. A method for preparing a powder metallurgy material, characterized in that: For producing the powder metallurgy material as claimed in claim 1, comprising the following steps: (1) Mixing: Put the raw material components of powder metallurgy materials into a mixer to mix the raw materials evenly; (2) Cold pressing: adding the raw materials mixed in step (1) into the mold cavity, pressing and molding, and then demolding; (3) Sintering: The blank obtained by demolding in step (2) is sintered in a sintering furnace under nitrogen protection.
6. The method for preparing a powder metallurgy material according to claim 5, characterized in that: in, In step 1), the mixing speed is 130-150 rpm and the mixing time is 1-2 h.
7. The method for preparing a powder metallurgy material according to claim 5, characterized in that: in, In step 2), the cold pressing pressure is 750-850 MPa, and the cold pressing holding time is 20-40 min.
8. The method for preparing a powder metallurgy material according to claim 5, characterized in that: in, Step 3) includes: Preheating stage: preheat the cold-pressed blank at a temperature of 110-130°C for 20 minutes; Heating stage: heating rate is 35-50℃ / min, heating to 850℃ and keeping warm for 45min; Sintering stage: heating rate 100℃ / min, heating to 1250-1320℃ and keeping warm for 2-3h.
9. The method for preparing a powder metallurgy material according to claim 5, characterized in that: in, In step 3), the nitrogen pressure is 0.3-0.5Mpa.
10. A bearing, characterized in that: The powder metallurgy material is prepared by the method for preparing the powder metallurgy material according to any one of claims 5 to 9.
Citation Information
Patent Citations
Powder metallurgy metal bearing material and manufacturing method thereof
CN103600060A
Method for preparing porous metal iron
CN104498761A
Method for preparing ceramsite through microwave sintering and curing of heavy metal chromium
CN107353034A
Porous magnetic ceramsite based on municipal sludge and preparation method and application thereof
CN110372330A
Long-service-life integrated shafting structure of miniature flywheel
CN111637168A